(untitled) (Advances in Military Technology, 2024)
The article provides up-to-date information on the latest Measurement and Signature Intelligence (MASINT) technologies to face Chemical, Biological, Radiological, Nuclear and Explosive (CBRNe) threats and their advancements exploitable by Intelligence and security practitioners. The primary emphasis is on CBRNe technologies, given their central role in MASINT. The discussion encompasses cutting-edge developments that exhibit significant potential in enhancing capabilities for the identification and mitigation of CBRNe risks. In addition, the document puts forth a set of recommendations which cover essential improvements and approaches to effectively address various aspects of CBRNe Intelligence. This comprehensive exploration aims to provide readers, including Intelligence and security practitioners, with valuable insights into the evolving landscape of MASINT technologies addressing the unique challenges posed by CBRNe threats.